Peningkatan Kemampuan Pemecahan Masalah Matematika Melalui Model Pembelajaran Auditory, Intellectualy, Repetition - Dodik Mulyono; Atika Nur Hidayati (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2020)
This study was aimed at investigating and analyzing the improvement of mathematical problem solving abilities through AIR Learning Model (Auditory, Intellectual, Repetition). The students’low interest in mathematics whicheffectedthe low ability to solve mathematical problemsbecame the main problems of this study. This isa Classroom Action Research (CAR) thatwas carried out in two cycles. The research subjects were students of class VIII-A of Odd Semester of SMP Negeri 26Bandar Lampungwith total number of 28 students. Data collection for each cycle usedtest and observation techniques. Data analysis techniques consisted of: 1) analysis of the results of observations, 2) analysis of the results of tests of problem solvingskills. To check the degree of data trust, this study usedtriangulation of other researcher, namely the headmaster, mathematics teacher, and students. Based on the results of data analysis,it couldbe concluded that there wasan increase in students' mathematical problem solving abilities. The imrovement could be seenfrom the pre-cycle in which there wereonly 2 students(7.14%) who could pass the testand26 students(92.86%) who did not passthe test. It was found anincrease in the first cycle in which there were4 students(14.29%) who could pass the testand 24 students(85.71) %) who did not passthe test, then in cycle II,there were 8 students(28.58%) who past the testand 20 students(71.43%) who did not pass the testand in cycle III,there were 20 students(71.43) who pass the testand 8 students(28.58%) who did not passthe test.